"Bottom-up" and "top-down" effects on reading saccades: a case study. Issue 10 (20th October 2003) - Upton, N J; Hodgson, T L; Plant, G T; Wise, R J S; Leff, A P
Abstract : Objective: To investigate the role right foveal/parafoveal sparing plays in reading single words, word arrays, and eye movement patterns in a single case with an incongruous hemianopia. Methods: The patient, a 48 year old right handed male with a macular sparing hemianopia in his left eye and a macular splitting hemianopia in his right eye, performed various reading tasks. Single word reading speeds were monitored using a "voice-trigger" system. Eye movements were recorded while reading three passages of text, and PET data were gathered while the subject performed a variety of reading tasks in the camera. Results: The patient was faster at reading single words and text with his left eye compared with his right. A small word length effect was present in his right eye but not his left. His eye movement patterns were more orderly when reading text with his left eye, making fewer saccades. The PET data provided evidence of "top-down" processes involved in reading. Binocular single word reading produced activity in the representation of foveal V1 bilaterally; however, text reading with the left eye only was associated with activation in left but not right parafoveal V1, despite there being visual stimuli in both visual fields. Conclusions: The presence of a word length effect (typically associated with pure alexia) can be caused by a macular splitting hemianopia. Right parafoveal vision is not critically involved in single word identification, but is when planning left to right reading saccades. The influence of top-down attentional processes during text reading can be visualised in parafoveal V1 using PET.